2022
DOI: 10.1002/ar.25134
|View full text |Cite
|
Sign up to set email alerts
|

Arterial circle of the brain in the common wildebeest (Connochaetes taurinus)

Abstract: The main aim of this study was to analyze the arterial circle of the brain and rostral epidural rete mirabile in specimens of the common wildebeest (Connochaetes taurinus). The arterial circle of the brain is a circulatory anastomosis that supplies blood to particular lobes of the brain and surrounding structures. The study was conducted on male and female adults (n = 12) by bilateral injection of an acetone solution of vinyl superchloride or latex LBS3060, which resulted in a cast of arteries of the head and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The arterial circle of the brain in buffalo is heart‐shaped as reported in Antilopinae and common wildebeest (Frąckowiak et al, 2015; Zdun et al, 2022), while in giraffe, it is roughly triangular (Frąckowiak & Jakubowski, 2008), and in camels, it is similar to the number ‘8’ (Kiełtyka‐Kurc et al, 2014). The current findings revealed that the rostral communicating artery in the buffalo was represented by a network of blood vessels as reported in small ruminants (Alsafy et al, 2017; Kapoor et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The arterial circle of the brain in buffalo is heart‐shaped as reported in Antilopinae and common wildebeest (Frąckowiak et al, 2015; Zdun et al, 2022), while in giraffe, it is roughly triangular (Frąckowiak & Jakubowski, 2008), and in camels, it is similar to the number ‘8’ (Kiełtyka‐Kurc et al, 2014). The current findings revealed that the rostral communicating artery in the buffalo was represented by a network of blood vessels as reported in small ruminants (Alsafy et al, 2017; Kapoor et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
“…The arterial circle of the brain in buffalo is heart-shaped as reported in Antilopinae and common wildebeest(Frąckowiak et al, 2015;Zdun et al, 2022), while in giraffe, it is roughlyF I G U R E 7 (a,b) Dorsolateral view of the brain showing the rostral cerebral artery (RCA), middle cerebral artery (MCA), rostral choroidal aretery (RChA), caudal cerebral artery (CCA), mesencephalic tectal branches (MTB), rostral cerebellar artery (RCbA), caudal cerebellar artery (CCbA) and optic tract (OT). (c) Caudomedial view of forebrain showing the distribution pattern of caudal cerebral artery (CCA) into rostral branch of CCA (blue arrow), caudal branch of CCA (red arrow) and terminal branches (yellow arrows).…”
mentioning
confidence: 75%
See 3 more Smart Citations